Early selection in Theobroma grandiflorum, aiming at tolerance to hypoxia - Rodrigues, Jardel Diego Barbosa [UNESP]; Alves, Rafael Moysés; Chaves, Saulo Fabrício da Silva (FapUNIFESP (SciELO), 2023)
Cupuassu (Theobroma grandiflorum)-based agroforestry system (AFS) can be used for restoration of vegetation around springs and riparian forests of water sources (rivers, streams, lakes etc.), subject to constant flooding. The objectives of this work were to study the relations between morphophysiological traits when flooding occurs, determining the most important to assess genotypes’ tolerance, and evaluate the ability of cupuassu genotypes to express alternative phenotypes and grow efficiently, in order to select materials capable of sustaining hypoxic conditions. The trial was carried out in a greenhouse, in a completely randomized design with a 16 x 2 (16 progenies and two water regimes) factorial scheme and four replications. Treatments started six months after the seedlings were transplanted. 15 traits related to vegetative development, biomass accumulation and physiology were measured for the experimental evaluation. Correlations and principal components were estimated to study the traits’ interrelationships and identify the most important to assist progeny selection. The results revealed that, among the evaluated traits, ten were sufficient to explain the variability within the population and four were elected as the most relevant to select the best progenies. 75% of the genotypes showed tolerance to partial flooding and based on performance and plasticity, we selected G174, G48 and G56 for a broader spectrum and G44, G47 and G51 for hypoxic conditions only. The promising evidence pointed out here will need to be corroborated with field tests, so that the cupuassu tree can be recommended in the recovery of environments subject to hypoxia.
Seleção precoce em Theobroma grandiflorum, visando tolerância à hipóxia
Keywords: Index terms: Flooding; path analysis; principal components; recovery of degraded areas